Clinical guidelines for the management of weight during pregnancy: a qualitative evidence synthesis of practice recommendations across NHS Trusts in England - Lucy Goddard; Nerys M. Astbury; Richard J. McManus; Katherine Tucker; Jennifer MacLellan (BMC, 2023)
Abstract Background Women who enter pregnancy with a Body Mass Index above 30 kg/m2 face an increased risk of complications during pregnancy and birth. National and local practice recommendations in the UK exist to guide healthcare professionals in supporting women to manage their weight. Despite this, women report inconsistent and confusing advice and healthcare professionals report a lack of confidence and skill in providing evidence-based guidance. A qualitative evidence synthesis was conducted to examine how local clinical guidelines interpret national recommendations to deliver weight management care to people who are pregnant or in the postnatal period. Methods A qualitative evidence synthesis of local NHS clinical practice guidelines in England was conducted. National Institute for Health and Care Excellence and Royal College of Obstetricians and Gynaecologists guidelines for weight management during pregnancy constructed the framework used for thematic synthesis. Data was interpreted within the embedded discourse of risk and the synthesis was informed by the Birth Territory Theory of Fahy and Parrat. Results A representative sample of twenty-eight NHS Trusts provided guidelines that included weight management care recommendations. Local recommendations were largely reflective of national guidance. Consistent recommendations included obtaining a weight at booking and informing women of the risks associated with being obese during pregnancy. There was variation in the adoption of routine weighing practices and referral pathways were ambiguous. Three interpretive themes were constructed, exposing a disconnect between the risk dominated discourse evident in the local guidelines and the individualised, partnership approach emphasised in national level maternity policy. Conclusions Local NHS weight management guidelines are rooted in a medical model rather than the model advocated in national maternity policy that promotes a partnership approach to care. This synthesis exposes the challenges faced by healthcare professionals and the experiences of pregnant women who are in receipt of weight management care. Future research should target the tools utilised by maternity care providers to achieve weight management care that harnesses a partnership approach empowering pregnant and postnatal people in their journey through motherhood.